The overall direct tax rate on earned incomes in Italy - SARCINELLI, M. (PSL Quarterly Review, 2014)
After the Second World War, direct taxation in Italy became oppressive and inequitable as a result of inflation and poor legislation. Following some initial reforms in the 1950s, rates have again increased, new taxes have been implemented and the design to transform direct taxation from an “objective” to a personal basis has only complicated the fiscal system. However, several ideas for fiscal reform have been adopted by the Five Year Development Programme for 1966-70 and are embodied in a bill now before the house of parliament. The present work analyses the proposed reforms considering the calculation of the overall rate, the average rate, the marginal rate and incentives to work, and the elasticity of yield and rates. The author concludes that while a mere consolidation of the present rates of the various taxes will lead to simplification and greater transparency, it will perpetuate injustices and anomalies in the rate structure. JEL: E62, E31, H21